Delirium prevention in early rehabilitation during acute hospitalization and implementation of programs specifically tailored to older patients with cognitive impairment: a scoping review with meta-analysis - Hauer, Klaus; Dutzi, Ilona; Werner, Christian; Bauer, Jürgen M.; Ullrich, Phoebe (Journal of Alzheimer's disease, 2024)
Background: No systematic review on delirium prevention within early, hospital-based rehabilitation on implementation of approaches specifically tailored for patients with cognitive impairment (PwCI), such as Alzheimer’s disease or vascular dementia,
Gesehen am 19.07.2024